Investigating the intention of pregnancy among women living with HIV and its effect on the early development of their HIV exposed infants - Moyo, Chido (Department of Public Health and Family Medicine, 2021)
Background: The increase in access and coverage of ART, including through prevention of mother-to-child transmission (PMTCT) programmes in Africa, has resulted in the reduction of vertical transmission, which has led to >95% of infants born to women living with HIV (WLHIV) in South Africa being born HIV uninfected. Concerns have however been raised regarding the health and development of HIV exposed and uninfected (HEU) infants. WLHIV in South Africa are more likely to have an unintended pregnancy compared HIV negative women. Unintended pregnancies continue to be a challenge towards the on-going strides and achievement of PMTCT goals. There is however a paucity of data on the investigations in research for the effect of unplanned pregnancy and early child development in South Africa. This research study focused on early infant development health outcomes of HIV exposed but uninfected (HEU).The aim of the study was to investigate the association between the intention of pregnancy among pregnant WLHIV, and the subsequent early child development of their HEU infants in Gugulethu, South Africa. Methods: This study used data from the “Long-term Adherence and Care Engagement” study (LACE; May 2017-Apr 2018), which provided long-term data from women who had initiated antiretroviral therapy (ART) during pregnancy. During pregnancy, the London Measure of Unplanned Pregnancy was used to assess pregnancy intentions. At 36-60 months postpartum, child development was assessed across six developmental domains using the Ages & Stages questionnaire (ASQ). Multivariate Linear regression models were used to examine the association between pregnancy intentions and subsequent child development, with results reported as regression coefficients (β) with 95% confidence intervals (CI). Results: A total of 250 mother-infant pairs completed assessments and were included in analysis. At enrolment, the median age for the women was 28.3 years, and 38% were married and/or cohabiting. Overall, based on the women's responses 58% of pregnancies were categorised as unplanned. Upon analysis, no associations were observed between pregnancy intention and all early child development domains p>0.05. Overall, infants with evidence of early developmental delay that scored below threshold (ASQ-3) were 8% for the gross motor domain, 19% for fine motor, 4% for communication, 15% for problem solving, and 7% for personal social domain. Whilst for the social emotional domain (ASQ: SE-2), two percent of infants scored above threshold and hence, had evidence of early developmental delay. Conclusions: Among women initiating ART during pregnancy, we observed no significant association between pregnancy intention and the early child development of their HEU infants. The findings of this research accentuate the need for targeted strategies towards psychosocial issues, and educational interventions for WLHIV and, for informed fertility decisions. Furthermore, the need for exploration of interventions to encourage infant-parent attachment and interaction for development, as well as the impact of pregnancy intentions on parenting behaviours.